Infrared interferometry to spatially and spectrally resolve jets in X-ray binaries - Markoff, S.; Russell, D.M.; Dexter, J.; Pfuhl, O.; Eisenhauer, F.; Abuter, R.; Miller-Jones, James; Russell, T.D. (OXFORD UNIV PRESS, 2020)
Infrared interferometry is a new frontier for precision ground-based observing, with new instrumentation achieving milliarcsecond (mas) spatial resolutions for faint sources, along with astrometry on the order of 10 microarcseconds (μas). This technique has already led to breakthroughs in the observations of the supermassive black hole at the Galactic centre and its orbiting stars, active galactic nucleus, and exo-planets, and can be employed for studying X-ray binaries (XRBs), microquasars in particular. Beyond constraining the orbital parameters of the system using the centroid wobble and spatially resolving jet discrete ejections on mas scales, we also propose a novel method to discern between the various components contributing to the infrared bands: accretion disc, jets, and companion star. We demonstrate that the GRAVITY instrument on the Very Large Telescope Interferometer should be able to detect a centroid shift in a number of sources, opening a new avenue of exploration for the myriad of transients expected to be discovered in the coming decade of radio all-sky surveys. We also present the first proof-of-concept GRAVITY observation of a low-mass XRB transient, MAXI J1820+070, to search for extended jets on mas scales. We place the tightest constraints yet via direct imaging on the size of the infrared emitting region of the compact jet in a hard state XRB.